Fatigue Resistance of Self-hardening Aluminium Cast Alloy. (2017) - Zavodska, Denisa; Tillova, Eva; Guagliano, Mario; Kucharikova, Lenka; Chalupova, Maria
Abstract: Cast aluminium alloys are widely used in fatigue critical structural applications, such as engine blocks, cylinder heads, chassis and suspension components, to improve automotive fuel economy. However, it may be difficult to use these alloys for parts that require a high fatigue strength and high reliability because of a large number of casting defects as porosity and microshrinkages exist in them. Fatigue properties of cast aluminium components are controlled by maximum defect size in the material. The larger maximum defect size, the lower the fatigue strength and life. Self-hardening Al-alloys (Al-Zn-Si-Mg alloys) introduce an innovative class of light Al-alloys. Fatigue properties of AlZn10Si8Mg cast alloy in the high cycle region were tested by rotating bending fatigue loading in a high cycle region with the used of parameters - frequency f = 40 Hz, temperature T = 20 ± 5 °C and stress ratio R = -1. Because of that large pores are near or at specimeńs surface and its dominant reason of fatigue crack initiation and propagation.